EFFECT OF WATER SALINITY AND POTASSIUM ON WHEAT GROWTH AND YIELD - Alhaidary , Hanaa Kh.; Ahmed, Halah Talib (Diyala Agricultural Sciences Journal, 2017)
The experiment was carried out at field crops Research Station in Diyala Directorate of Agriculture during the winter season of 2013 and 2014. The aim of the experiment was to study the effect of potassium foliar on wheat crop tolerance to levels of water salinity in different stages of growth, according to the scale of Zadoks for small grains and this impact on some traits yield and yield components of wheat (IPA 99 var.). Randomized Complete Block Design with three replications by Split-plot arrangement was used for the experiment. The main plots included four levels of water salinity treatments (water concentrations of salt 7, 14, 21 dS m-1, river water). While Sub-plots included potassium foliar treatments according to the stages of crop growth. The results of the experiment showed negatively effect of water salinity S3 level (21 dS m-1) on the mean of grain yield, which was significantly lower rate (55.90 and 55.85 %) for two seasons respectively. The treatment (K6) potassium foliar in two stages booting and flowering Excelled in grain yield. As treatment (K7) potassium spray in elongation stage, booting and flowering excelled, in 1000-grain weight in two seasons. The combination S0K6 gave the highest average for spike number 304.4 .97.5 spike m-2 respectively in two seasons, and it excelled in number of grain in spike in season one, while S0K5 treatment were recorded the significantly highest rate in grain yield in two seasons and number of grain in spike in second season. The combination S3K0 recorded the significantly lowest average of number of spikes, weight of thousand grain and grain yield in two seasons